O que exatamente torna os museus de hoje tão diferentes, tão atraentes? - Ivo André Braz (Midas: Museus e Estudos Interdisciplinares)
The present article affirms the importance of participation in the museological experience. This affirmation implies, however, that participation should not be assumed as a pre-given fact, but requires a critical reflection on its own bases. Firstly, we will examine how today’s museum presents itself as a place of attraction, activity and performativity, essentially different from the authoritarian and pedagogical museum of the past. Then, we will try to complicate this image through an interdisciplinary exercise of co-implication between the museum's narrative and some theoretical approaches from other areas of knowledge. This will lead us to a double reading where the museum seems to be always marked by something that is lacking or in excess. A “lack” of museum where a metaphysic of participation connects intentionality and meaning through logics of activation. An “excess” of museum where an ever successful performativity constitutes the paradigm of a contemporary situation that can be qualified as bio-aesthetic. However, this double reading doesn't necessarily mean an impasse. The recognition of the supplementary between museum and public embodies the possibility of untying participation from intentionality and productivity. To do so is to open the museum’s text to elements forced to stay on its margins and to reinforce the very idea of participation.